Association between meal frequency with others and psychological distress during the COVID‐19 pandemic: A cross‐sectional study. Issue 4 (27th November 2022) - Tsuji, Rikako; Nishi, Daisuke; Sasaki, Natsu; Akiyama, Hiroto; Kuroda, Reiko; Tsuno, Kanami; Imamura, Kotaro; Kawakami, Norito
Abstract: Aim: Previous studies evaluated the association between eating alone and mental health mainly in older people and adolescents. This study aimed to evaluate the association between dinner frequency with others and psychological distress during the COVID‐19 outbreak among the Japanese working population. Methods: Data were acquired from a prospective online cohort study (the Employee Cohort Study in the COVID‐19 pandemic in Japan) conducted in February 2021 as a cross‐sectional design. Dinner frequency with others was categorized into five groups: "almost daily, " "4–5 times per week, " "2–3 times per week, " "once per week, " and "less than once per week, " setting them as a predictor variable. Modified Poisson regression was performed to calculate the prevalence ratio of psychological distress with multiple imputation for missing data. Global fear and worry about COVID‐19 were adjusted as a covariate. Results: A total of 1171 participants completed the questionnaire. Respondents who ate dinner with others "almost daily" had the least psychological distress than those who ate with others "4–5 times, " "2–3 times, " and "once per week" in the crude model (prevalence ratio (95% CI): 1 [reference], 1.34 [1.08–1.67], 1.40 [1.15–1.69], 1.44 [1.12–1.85], respectively). The association was comparable after adjusting for global fear and worry about COVID‐19. Conclusions: Among those who ate dinner with others at least once a week, those who ate with others "almost daily" had the least psychological distress. The association was comparable after adjusting for global fear and worry about COVID‐19. Further study is needed on why those who eat with others less than once a week may have a lower prevalence ratio of having mental distress. Abstract : Among those who ate dinner with others at least once a week, those who ate with others "almost daily" had the least psychological distress. The association was comparable after adjusting for global fear and worry about COVID‐19.